2003
DOI: 10.1038/sj.embor.embor850
|View full text |Cite
|
Sign up to set email alerts
|

COP9 signalosome components play a role in the mating pheromone response of S. cerevisiae

Abstract: CORRECTIONIn the December 2002 issue of EMBO reports, we published an error about the name and contribution of one of the authors, Elah Pick. The second footnote should have read, "V. Maytal-Kivity, R. Piran and E. Pick contributed equally to this work."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 21 publications
1
46
0
1
Order By: Relevance
“…In another example, we predicted that Csn12 was not a component of the COP9 signalosome, which is involved in deneddylation (27). Consistent with this, Maytal-Kivity et al (64) demonstrated that Csn12 is the only component of this complex that is not required for the deneddylation activity. Furthermore we found that Csn12, but not other signalosome subunits, is required for efficient mRNA splicing at a number of genes in budding yeast, 4 suggesting that Csn12 plays multiple cellular roles and may not be an integral member of the complex.…”
Section: Contribution Of Each Data Source For Predictingsupporting
confidence: 58%
“…In another example, we predicted that Csn12 was not a component of the COP9 signalosome, which is involved in deneddylation (27). Consistent with this, Maytal-Kivity et al (64) demonstrated that Csn12 is the only component of this complex that is not required for the deneddylation activity. Furthermore we found that Csn12, but not other signalosome subunits, is required for efficient mRNA splicing at a number of genes in budding yeast, 4 suggesting that Csn12 plays multiple cellular roles and may not be an integral member of the complex.…”
Section: Contribution Of Each Data Source For Predictingsupporting
confidence: 58%
“…The budding yeast Saccharomyces cerevisiae possesses an alternative CSN complex. This includes as the only significantly conserved subunit the homolog of Csn5 [18]. Csn5 is the intrinsic CSN enzyme activity including MPN and a JAMM domain for a metalloprotease activity.…”
Section: Csn Organisation and Intrinsic Functionmentioning
confidence: 99%
“…The deneddylation activity resides within CSN subunit CSN5, which to date is the only CSN subunit with a known biochemical activity. CSN5 has an interesting feature in that it is present in all eukaryotes not only as a subunit of CSN but also as a monomer (Freilich et al, 1999;Mundt et al, 1999Mundt et al, , 2002Maytal-Kivity et al, 2002;Oron et al, 2002;Dohmann et al, 2005). Interestingly, although csn subunit mutants typically lack the residual CSN complex and frequently also the residual CSN subunits, the CSN5 monomer is always maintained in these mutants (with the obvious exception of csn5 mutants).…”
mentioning
confidence: 99%